Categorization of Heritage Tourism: A Conceptual Overview - Pandeeswari, B.; Abbas, R. (Journal of Neonatal Surgery, 2025)
Tourism has existed for centuries, but it gained unprecedented popularity in the twentieth century due to globalization, improved transportation, and rising disposable incomes. People travel for religious, health, leisure, learning, or cultural exploration. Pilgrimage and medical tourism represent travel for spiritual or health purposes, whereas heritage tourism emphasizes visiting sites of historical, cultural, and traditional significance. These travels not only generate revenue but also influence the social, economic, and cultural fabric of host communities.Heritage tourism specifically focuses on places and practices that authentically represent a community’s past and present. According to the National Trust for Historic Preservation, heritage tourism involves “traveling to experience the places, artifacts, and activities that authentically represent the stories and people of the past and present, including cultural, historical, and natural resources.” This paper explores the meaning, classifications, and significance of heritage tourism, highlighting its economic, social, and cultural implications.